Case Report: Acute Ophthalmic Herpes Zoster (HZO) in a Child - Ulfadila, Lulu Hasna (Indonesian Journal of Advanced Research, 2024)
Herpes zoster (HZ) is a unilateral and dermatomal reactivation of the varicella zoster virus. The incidence of HZ in those under 9 years of age is 0.74/1000. HZO affects the ophthalmic nerve, causing abnormalities around the eyes. There has been a reported case of a 6 year old child who came with complaints of clusters of elasticity and pain in the stomach and left eye. Patients diagnosed with acute HZO were given oral therapy with Acyclovir tablets 5x400 mg for 7 days, Hervis eye ointment 5x a day, Acyclovir skin ointment 5x a day, and Paracetamol syrup 3x1 spoon. Treatment is given with the aim of speeding up the lesion healing process, reducing complaints of acute pain, reducing the risk of PHN complications, and improving the patient's quality of life. Fast and appropriate management is expected to have a good impact on the patient's treatment response.